Beyond the Makerspace Making and Relational Rhetorics - Shivers-McNair, Ann (Sweetland Digital Rhetoric Collaborative, 2021)
Makerspaces-local workshops that offer access to and training on fabrication technologies, often with a focus on creativity, education, and entrepreneurship-proliferated in the 2010s, popping up in cities across the world. Beyond the Makerspace is a longitudinal, ethnographically informed study of a particular Seattle makerspace that begins in 2015 and ends with the closing of the space in 2018. Examining acts of making with objects, tools, words, and relationships, Beyond the Makerspace reads making as a kind of rhetoric, or meaning-making work, and argues that acts of making things are rhetorical in the sense that they are culturally situated and that they mark boundaries of what counts as making and who counts as maker. By focusing on a particular makerspace over time, Shivers-McNair attends to a changing cohort of makerspace regulars as they face challenges of bringing their vision of inclusivity and diversity to fruition, and offers an examination of how makers are made (and unmade, and remade) in a makerspace. Beyond the Makerspace contributes not only to our understanding of making and makerspaces, but also to our understanding of how to study making-and meaning making, more broadly-in ways that examine and intervene in the marking of difference. Thus, the book examines what (and whose) values and practices we are taking up when we identify as makers or when we turn a writing classroom or a library space into a makerspace.